Treatment and Prevention Strategies for Patients with Gynecological Malignancies During the COVID-19 Pandemic - Yang J (Risk Management and Healthcare Policy, 2020)
Jiang Yang,* Jin Liu,* Suting Li, Li Hong Department of Obstetrics and Gynaecology, Renmin Hospital of Wuhan University, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Hong Email drhongli77@gmail.comAbstract: COVID-19 has the characteristics of rapid onset, strong infectivity, and fast course change, which has caused a worldwide pandemic. Now, our hospital and department have implemented a series of efficacious stratagems to control the spread of the COVID-19. However, the daily-increasing cases are continuously at an extraordinary level, which mean the requirement and mission to prevent and control the pandemic are enormous and urgent. However, because of the urgency of the disease and the timeliness of treatment, gynecological tumor patients cannot be administered in the hospital until the pandemic situation could be controlled entirely. Consequently, this review proposes the following suggestions and our experience about preventing and controlling of COVID-19 and the treatment for patients with gynecological tumors in gynecology departments.Keywords: COVID-19, prevention and control strategies, treatment, strategy